Manifestations of Neoosmanist Ambitions in Contemporary Regional Policy of Turkey - Y. Kudryashova (Международная аналитика, 2015)
Turkey carried away by the role of the model for Sunni states aimed at becoming the leader of Islamic world and reestablishing the Ottoman Empire’s sphere of influence. Ankara distinctly changed priorities of its foreign policy in favor of the Middle East and pursued a course of gradual dissociation from the West subject to its own views at world and regional situation. Ankara’s task was not to exceed the limits of Western alliance, but for all that to advance at most its national interests. Turkey’s political leaders systematically used any opportunity to promote neoosmanist aspirations and the model of Turkish democracy in the Middle East and Northern Africa. The dynamic development of Turkish economy supported this process. However at this time the goals of Turkish neoosmanist policy are unachievable because of their excessive ambition and lack of resources for their realization.